2021
DOI: 10.24818/basiq/2021/07/060
|View full text |Cite
|
Sign up to set email alerts
|

How Do Europeans Travel and Spend? A Pre-COVID Cluster Approach

Abstract: The planning options for tourist activities take into account the potential tourists' behavior and travel preferences. In this context, the study presents a systematic framework on the travel preferences of European tourists. These are highlighted by the number and types of trips, in which priority is assigned to those oriented towards rural and mountain areas, as well as by trip expenditure related to basic services (accommodation and transport). The analysis involves a clustering of EU countries, taking into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In order to ensure the necessary framework for a sustainable development of the Romanian coastal area, a balance must be ensured between the economic development, the protection and conservation of the natural, socio-cultural environment and meeting the needs of the local communities, given that the concept of sustainability covers virtually all the areas and sectors in which a development process takes place (Petrişor, 2017). Therefore, coastal, and maritime tourism must bring benefits to the local communities, being well known that tourism activity implies a complex of services engaged in a local economy, and their unsustainable development can put great pressure on the environment (Gogonea et al, 2021). Several studies in the specialized literature have identified, using exploratory methods, the similarities and differences between economic activities, so that in terms of different economic and financial indicators, they can be taken as benchmarks in business design at the level of the local economy (Mirea and Aivaz, 2016;Munteanu Florea and Aivaz, 2017).…”
Section: Scientific Literature Reviewmentioning
confidence: 99%
“…In order to ensure the necessary framework for a sustainable development of the Romanian coastal area, a balance must be ensured between the economic development, the protection and conservation of the natural, socio-cultural environment and meeting the needs of the local communities, given that the concept of sustainability covers virtually all the areas and sectors in which a development process takes place (Petrişor, 2017). Therefore, coastal, and maritime tourism must bring benefits to the local communities, being well known that tourism activity implies a complex of services engaged in a local economy, and their unsustainable development can put great pressure on the environment (Gogonea et al, 2021). Several studies in the specialized literature have identified, using exploratory methods, the similarities and differences between economic activities, so that in terms of different economic and financial indicators, they can be taken as benchmarks in business design at the level of the local economy (Mirea and Aivaz, 2016;Munteanu Florea and Aivaz, 2017).…”
Section: Scientific Literature Reviewmentioning
confidence: 99%